Patient reported health status and all-cause mortality in patients with coronary heart disease. (28th October 2017) - Raymakers, Adam J N; Gillespie, Paddy; Murphy, Edel; Cupples, Margaret E; Smith, Susan M; Murphy, Andrew W; Griffin, Matthew D; Benyamini, Yael; Byrne, Molly
Abstract: Purpose: Patients with coronary heart disease (CHD) experience reduced quality of life which may be associated with mortality in the longer term. This study explores whether patient-rated physical and mental health status was associated with mortality at 6-year follow-up among patients with CHD attending primary care in Ireland and Northern Ireland. Methods: This study is a secondary data analysis of patients with CHD recruited to a cluster randomized controlled trial from 2004 to 2010. Data collected included patient-rated physical component summary (PCS) and mental component summary (MCS) scores of health status (from the 12-Item Short-Form Health Survey (SF-12)), demographics and clinical parameters at baseline, and all-cause mortality at 6-year follow-up. Multivariate regression was conducted using generalized estimating equations (GEE) with a log-link function. Results are presented as odds ratios (ORs) and 95% confidence intervals (CIs). Results: The study consisted of 762 individuals with mean age 67.6 years [standard deviation (SD): 9.8], and was 29% female. Mean baseline SF-12 mental (MCS) and physical (PCS) component scores were 50.0 (SD: 10.8) and 39.6 (SD: 11.2), respectively. At 6-year follow-up, the adjusted OR for the baseline MCS for mortality was 0.97 (95% CI: 0.95–0.99) and for the PCS 0.97 (95% CI: 0.95–0.99). For every five-point increase in MCS and PCS scores, there was a 14% reduction in the likelihood of all-cause mortality. Conclusions: Overall, the magnitude of effect for both mental health status and physical health status was similar; higher scores were significantly associated with a lower risk of mortality at 6-year follow-up.